Reversible cause of complete heart block: An unusual presentation of thyrotoxicosis - Nattusamy Loganathan; Somasundaram Maheswari; Kalliappan Tamilarasu; Gopalan Rajendiran (SpringerOpen, 2016)
Thyrotoxicosis is a clinical entity that is often very difficult to diagnose without biochemical confirmation, as its clinical features can be highly varied. It is more common in women, with a female to male ratio of up to 5 : 1 between the ages of 20 and 40. Thyroid hormone is important at a cellular level, affecting nearly every type of tissue in the body. Very rarely it can cause heart blocks. We report a case of complete heart block associated with thyrotoxicosis that reverted to sinus rhythm with medical management alone.